A necessary review to understand the present: policies in favour of civic education in contemporary Spain - Santiago Esteban Frades (Avances en Supervisión Educativa, 2009)
In spite of the drawbacks for the development of civic education and the lack of a well-established political and intellectual movement committed to it, there have been policies, regulations, associative forces and authors that have promoted in Spain education for citizenship for the last two hundred years. However, we must be conscious that these efforts have actually had little repercussion on the educational system as a whole and on Spanish people in general terms.